Study of Information seeking on nursing students of Mazandaran Medical Science University and Related Barriers - MousaviChalak, Afshin; Riahi, Aref; Zare, Amin (Advances in Nursing & Midwifery, 2018)
Abstract Introduction: Increasing Information and recognize its values in personal and professional life for each person brings challenges and barriers that how people can access to information and it is necessary for them to obtain some special skills in information seeking process. This study aimed to examine information seeking of Mazandaran Medical Science University Nursing Student’s and identified their barriers to access to information. Materials and Methods: This is applied and survey-descriptive (Sectional) study. Statistical populations include all Nursing student of Mazandaran medical science university (faculty of nursing in Sari and Behshahr). We use self-questionnaire that made in 5 sections, to collect data and use SPSS and Statistical test to analysis them. Findings: Findings show that most important motivation of examined student to access and search their own information was "do homework (Educational Activities)". We funded that "Books" and "Journals" with average of 4.10 and 3.91 and also "General search engines" identified as the most important resources and channels to access to information. "University equipment problems" mentioned by nursing student as the most challenges in their information seeking process. Conclusion: This study shows that nursing students needs to receive information from the formal and valid channels because of quality and quantity incrassating of suitable information, related to their personal, educational, and professional life. Planning and making policy by management and masters of Mazandaran Medical Science University can be useful for student access to information with developing of information channels.